1986
DOI: 10.1152/jappl.1986.61.1.165
|View full text |Cite
|
Sign up to set email alerts
|

Muscle glycogen utilization during prolonged strenuous exercise when fed carbohydrate

Abstract: The purpose of this study was to determine whether the postponement of fatigue in subjects fed carbohydrate during prolonged strenuous exercise is associated with a slowing of muscle glycogen depletion. Seven endurance-trained cyclists exercised at 71 +/- 1% of maximal O2 consumption (VO2max), to fatigue, while ingesting a flavored water solution (i.e., placebo) during one trial and while ingesting a glucose polymer solution (i.e., 2.0 g/kg at 20 min and 0.4 g/kg every 20 min thereafter) during another trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
648
9
29

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 833 publications
(730 citation statements)
references
References 24 publications
44
648
9
29
Order By: Relevance
“…Whereas it was generally accepted that exogenous CHO oxidation rates were thought to be limited at approximately 1 g/min due to saturation of intestinal glucose transporters, it is now known that exogenous CHO oxidation rates can increase to 1.8 g/min with the addition of sucrose or fructose to the CHO blend [38]. When taken together, it is currently thought that CHO feeding during exercise may therefore augment exercise performance via multiple mechanisms consisting of muscle glycogen sparing [39], liver glycogen sparing [40] and maintenance of plasma glucose and CHO oxidation rates [41]. It is noteworthy, however, that exogenous CHO feeding during exercise also improves performance when exercise duration is <60 minutes [42], an effect that is not apparent when glucose is directly infused to the bloodstream during exercise [43].…”
Section: Is Carbohydrate Still King?mentioning
confidence: 99%
“…Whereas it was generally accepted that exogenous CHO oxidation rates were thought to be limited at approximately 1 g/min due to saturation of intestinal glucose transporters, it is now known that exogenous CHO oxidation rates can increase to 1.8 g/min with the addition of sucrose or fructose to the CHO blend [38]. When taken together, it is currently thought that CHO feeding during exercise may therefore augment exercise performance via multiple mechanisms consisting of muscle glycogen sparing [39], liver glycogen sparing [40] and maintenance of plasma glucose and CHO oxidation rates [41]. It is noteworthy, however, that exogenous CHO feeding during exercise also improves performance when exercise duration is <60 minutes [42], an effect that is not apparent when glucose is directly infused to the bloodstream during exercise [43].…”
Section: Is Carbohydrate Still King?mentioning
confidence: 99%
“…However, fat oxidation may not be sufficient to maintain the power output required during the cycling time-to-exhaustion test. In fact, a number of studies have reported that exogenous carbohydrate supplementation, especially when muscle glyco-Carbohydrate availability and time to exhaustion www.bjournal.com.br gen concentrations are low, can maintain blood glucose and total carbohydrate oxidation and delay the onset of fatigue (4)(5)(6)(7)(8)(9). Therefore, while carbohydrate-loading diets are associated with improved endurance capacity, ascribed mainly to maintenance of a high rate of carbohydrate oxidation throughout exercise, low carbohydrate diets have been shown to impair endurance exercise capacity, which has been ascribed to anticipated reduction of endogenous carbohydrate availability and to a decreased rate of carbohydrate oxidation (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The elevated plasma adrenaline-to-insulin ratio, due to fasting, increases circulating FFA concentration via stimulation of peripheral lipolysis (3,19,23). At the same time, reduced liver glycogen content impairs glucoregulation (15,16), which suppresses the input of blood-borne glucose in energy turnover. Thus during exercise in the fasted state (F), the rate of fat oxidation for a given submaximal exercise intensity is significantly increased (6,19).…”
mentioning
confidence: 99%